PENGARUH TARIF KAMAR TERHADAP KEPUASAN DAN MINAT PASIEN DALAM PEMBELIAN ULANG JASA RAWAT INAP DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Soesanto, Harry (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1998)
The National development being implemented in six PELITA bring a good result in health care sector. The hospital is getting isolate as it own definite the tariff for services which have been given to consumer; because not all hospital stand alone to definite the services. As an effect, definite tariff is first tariff and the definite of consumer tendency to come with comfirmable tariff. This research has a tendency (1) to identify room tariff influence, and the relationship between patient satisfaction and patient willingness in rebuying in patient services in Panti Rapih hospital; (2) to identity consumer behaviour about patient satisfaction and to repurchase for health services in Panti Rapih hospital.Research design applied was on observational research (non experimental), and the research subject in patient. Sample was drawn as purpossive with definitelly criteria. Data were collect through from question which has been fill by responden. And result will be examination as qualitative and quantitative with SPSS/PC + program. The result showed that (1) subject desire to use Panti Rapih hospital and the result has been influence by satisfied servent depending with room tariff; (2) research subject show that patient interest in rebuying in patient services, big enough to prediction behavior in decision making.Based on the result, it was concluded that patient interest in rebuying depending by patient satisfied, but a low cost of room tariff has been ignored.Thus a room tariff is not the only behavior reason to use Panti Rapih hospital, and not support by result of research calculation which mean that hypothesis has been denied.